Association between Noise Exposure and Hyperthyroidism Risk: A Retrospective Case-Control Study - Ming Gao; Jianing Yi; Luyao Liu; Lin Xu (Noise and Health)
Background: Environmental and lifestyle factors may influence hyperthyroidism prevalence. This research sought to explore the association between noise exposure and the risk of hyperthyroidism. Methods: This retrospective case–control study was conducted in two hospitals in China between January 2022 and December 2023. Among the 128 participants enrolled, 64 were hyperthyroidism patients (the hyperthyroidism group), and 64 had normal thyroid function (the control group). The variables compared between the groups included body mass index (BMI), residence areas (urban/rural), average noise levels, noise compliance rates, iodized salt intake, and anxiety levels (Self-Rating Anxiety Scale, SAS). Multivariable logistic regression was performed to identify the risk factors for hyperthyroidism. Results: The hyperthyroidism group showed significantly higher residential noise level, SAS score, excessive iodized salt intake rate, and urban residential rate compared with the control group (P < 0.05). The hyperthyroidism group also showed a lower noise compliance rate and BMI compared with the control group (P < 0.05). Urban participants exhibited higher noise levels, excessive iodized salt intake rate, hyperthyroidism incidence, SAS score, and lower noise compliance rates compared with the rural participants (P < 0.05). Logistic regression analysis revealed that high noise level (OR = 1.103, 95% CI 1.024–1.187) and high anxiety level (OR = 1.292, 95% CI 1.136–1.329) are risk factors for hyperthyroidism. High noise compliance rate (OR = 0.787, 95% CI 0.060–0.845) and rural residence (OR = 0.643, 95% CI 0.078–0.829) are protective factors for hyperthyroidism. Conclusion: This study underscored noise exposure and anxiety as modifiable risk factors for hyperthyroidism. Strict environmental noise regulations and enhanced public health education are necessary to reduce the risk of hyperthyroidism.